Pretransplant Quality of Life and Post-Transplant Survival in Adolescents with Cystic Fibrosis. (26th October 2021) - Bernstein, Ruth; Lynn, Courtney; Faro, Albert; Barker, David; Quittner, Alexandra
Abstract: Objective: Cystic fibrosis (CF) is the most common indication for pediatric lung transplantation and the third most common for adults. The selection of candidates and timing of transplant is challenging and whether there is a survival benefit of this procedure for pediatric patients is controversial. Use of the Cystic Fibrosis Questionnaire-Revised (CFQ-R), a well-validated, disease-specific quality of life measure may improve pretransplant referral decision-making. Methods: This multicenter study evaluated whether specific domains on the CFQ-R (i.e., Physical Functioning, Respiratory Symptoms), assessed pretransplant, predicted survival 4-year post-transplant ( n = 25). A two-step Cox regression, with physical predictors entered in step one (i.e., age, CF-related Diabetes, FEV1 % predicted) and the Physical Functioning and Respiratory Symptoms CFQ-R scales entered in step two, was used to assess whether the CFQ-R explained additional and unique variance. Receiver Operating Characteristic (ROC) curves were used to assess the sensitivity and specificity of optimal cut-points of significant CFQ-R domains. Results: The Respiratory Symptoms scale predicted survival 4-year post-transplant (Exp( B ) = 0.38, 95% CI = 0.14–1.01; area under the curve = 0.87) and once it was added to the model, no other individual predictors were significant. The incremental improvement beyond the physical parameters approached but did not reach statistical significance ( χ 2 Δ = 5.79, p = .06). Conclusions: This study suggested that including patient-reported outcomes could aid pretransplant referral decision-making. The Respiratory Symptoms scale in particular may serve as a useful tool to help determine when to refer and evaluate an individual for transplant.